Stock de carbono en la biomasa de seis especies forestales representativas de 4 parcelas del arboretum “el huayo”, ciefor, Puerto Almendra, Loreto-Perú, 2024 - Fasabi Ramírez, Maximo Alfonso (Universidad Nacional de la Amazonía Peruana, 2024)
The study was conducted in four plots (VI, VII, VIII, and IX) of the “El Huayo” Arboretum, located in a medium terrace forest within CIEFOR, Puerto Almendra, San Juan Bautista, Perú. All forest species were evaluated to determine those with the highest importance value index (IVI) or greater representativeness. Six species were identified as the most abundant and dominant: Eschweilera decolorans Sandwith (7.41% IVI), Nealchornea yapurensis Huber (3.77% IVI), Pourouma cucura Standl. & Cuatrec. (3.60% IVI), Parkia nitida Miq. (3.36% IVI), Cedrelinga cateniformis (Ducke) Ducke (2.30% IVI), and Triplaris peruviana Fisch. & C. A. Mey. ex C. A. Mey. (1.99% IVI). These species exhibited the highest carbon storage in aboveground biomass, accounting for a subtotal of 144.69 tnC, with a total carbon stock of 406.54 tnC in the study area. The results show a high degree of variability among the collected data, which is highly heterogeneous. In this context, Eschweilera decolorans Sandwith displayed the highest carbon storage in aboveground biomass compared to the other species. Since the data do not follow a normal distribution, the differences in carbon content stored in the biomass of the six most representative forest species are statistically significant. The studied species exhibit varying amounts of carbon storage in aboveground biomass, depending on species-specific diameter measurements and the applied allometric equations.

El estudio se basó en 4 parcelas (VI, VII, VIII y IX) del Arboretum “EL Huayo” de bosque de terraza media, del CIEFOR, Puerto Almendra, San Juan Bautista, Perú. Se evaluó a todas las especies forestales para determinar el alto valor de importancia o con mayor representatividad, siendo seis especies con mayor abundancia y dominancia que son Eschweilera decolorans Sandwith (7,41% IVI), Nealchornea yapurensis Huber (3,77% IVI), Pourouma cucura Standl. & Cuatrec. (3,60% IVI), Parkia nitida Miq (3,36% IVI), Cedrelinga cateniformis (Ducke) Ducke (2,30% IVI) y Triplaris peruviana Fisch. & C. A. Mey. ex C. A. Mey. (1,99% IVI), siendo estas especies con mayor contenido de almacenamiento de carbono en la biomasa aérea, que hace un subtotal de 144,69 tnC y en total en el área tenemos 406,54tnC. El estudio muestra gran variabilidad de los datos diferentes entre sí, que se encuentra en un nivel muy alto y son muy heterogéneas, en ese sentido, Eschweilera decolorans Sandwith contiene el mayor almacenamiento de carbono en la biomasa aérea más que el resto de las especies. Los datos no son normales y es por ello que existe significancia en el contenido de carbono almacenado en la biomasa de seis especies forestales más representativa. Las especies estudiadas presentan diferentes cantidades de carbono almacenado en la biomasa aérea, de acuerdo a las diferentes medidas de diámetros según especies y según la alometría usada.
Keywords: Secuestro de carbono; Árboles forestales; Biomasa; Parcelas; Arboretos; https://purl.org/pe-repo/ocde/ford#4.01.02